1997
DOI: 10.1182/blood.v89.6.1870
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor, a Possible Paracrine Growth Factor in Human Acute Myeloid Leukemia

Abstract: Vascular endothelial growth factor (VEGF ) is a multifunctional cytokine involved in angiogenesis, inflammation, and wound healing. It is secreted by a variety of tumor cell lines, including hematopoietic lines. Therefore, we investigated expression of VEGF and its receptors on fresh leukemic blasts. VEGF-specific transcripts were detected by polymerase chain reaction (PCR) in 20 of 28 patients with de novo acute myeloid leukemia (AML) and in 3 of 5 patients with secondary AML. Using immunocytochemistry, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
147
0
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(164 citation statements)
references
References 24 publications
8
147
0
9
Order By: Relevance
“…Accordingly, conditioned medium from VEGF-producing leukaemic cell lines was found to stimulate proliferation and/or chemotaxis in cultured endothelial cells (Vacca et al, 1998). VEGF mRNA and protein were also expressed in freshly isolated blasts from most patients with AML, and supernatants of fresh leukaemic cells from patients with AML contained significantly more VEGF than supernatants from bone marrow cells of normal donors (Fiedler et al, 1997a). VEGF paracrine growth stimulation of AML blasts in vivo was suggested by its stimulation of human umbilical cord endothelial cell production of granulocyte-macrophage colony-stimulating factor, a known stimulator of AML blast proliferation (Fiedler et al, 1997a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Accordingly, conditioned medium from VEGF-producing leukaemic cell lines was found to stimulate proliferation and/or chemotaxis in cultured endothelial cells (Vacca et al, 1998). VEGF mRNA and protein were also expressed in freshly isolated blasts from most patients with AML, and supernatants of fresh leukaemic cells from patients with AML contained significantly more VEGF than supernatants from bone marrow cells of normal donors (Fiedler et al, 1997a). VEGF paracrine growth stimulation of AML blasts in vivo was suggested by its stimulation of human umbilical cord endothelial cell production of granulocyte-macrophage colony-stimulating factor, a known stimulator of AML blast proliferation (Fiedler et al, 1997a).…”
Section: Discussionmentioning
confidence: 98%
“…Bellamy et al (1999) reported moderate to strong expression of VEGFR-1 mRNA in five of 12 leukaemia cell lines, but no VEGFR-2 mRNA expression in any of the 12 lines. Similarly, when studying VEGFR expression in fresh leukaemic blasts from patients with AML, Fiedler et al (1997a) found VEGFR-1 mRNA in 50% of cases and VEGFR-2 mRNA in 20% of cases. Ratajczak et al (1998) found detectable levels of VEGFR-1 mRNA in all samples examined from 15 patients with chronic-phase chronic myeloid leukaemia (CML) and seven patients with AML.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) and its receptors are expressed in leukaemic cells from most patients with AML, and serum VEGF levels are significantly higher than those in normal controls (Fiedler et al, 1997). High cellular VEGF levels are also a negative prognostic factor in AML (Aguayo et al, 1999).…”
mentioning
confidence: 99%
“…The close proximity of the islands of haematopoietic cells to the normal bone marrow vessels (Branemark, 1968) and the common origin of haematopoietic and vascular endothelial cells during embryonic development (Choi et al, 1998) attest to an intimate liaison, in both a physical and a conceptual sense, between the bone marrow haematopoietic function and its vascular bed (Branemark, 1968). The production of haematopoietic growth factors by endothelial cells (Fiedler et al, 1997;De Bont et al, 2001;Keyhani et al, 2001) is in harmony with this concept. Recently, interest in bone marrow vascularity has revived owing to the realization that leukaemic cells might depend upon vascular support just like normal haematopoietic cells and the cells of most solid tumours (Mangi & Newland, 2000;Keyhani et al, 2001;Ribatti et al, 2001).…”
Section: Discussionmentioning
confidence: 77%